The frequency of transplacental Varicella-Zoster Virus transmission after primary maternal infection - Isaković Vuk; Knežević Aleksandra (Medicinski Podmladak, 2020)
Introduction: Varicella-Zoster Virus (VZV) is a very important cause of perinatal infections. The greatest risk for perinatal infection is a primary infection during pregnancy with possible transplacental transmission of the virus and the onset of congenital varicella syndrome or neonatal varicella. Aim: The objective of this study was to evaluate the frequency of transplacental VZV transmission in pregnant women in our population. Material and Methods: The study included 50 samples of amniotic fluid of pregnant women with suspected fetal varicella or VZV vertical transmission. The presence of the virus was determined by the PCR method with primers for DNA VZV gene 71. The procedure involved the extraction of DNA, PCR and gel electrophoresis for visualization of specific PCR products. Results: The presence of VZV was demonstrated in 14% (7/50) of the amniotic fluid samples. Transmission of the virus was detected in all three trimesters of pregnancy. Statistical significance was not shown between the referral diagnosis, age of pregnant women and gestational age of the pregnancy and VZV positivity. Conclusion: The results of this study showed a low prevalence of VZV vertical transmission during the eight-year period, the lowest in the second trimester, and no statistical significance in accordance with diagnosis, gestational age, and VZV positivity. Screening is significant for VZV during the generative period of women. Those who are seronegative for VZV during pregnancy are at high risk for vertical transmission and are indicative for immunoglobulin therapy. If intrauterine infection is confirmed, adequate antiviral therapy is required.